A vestimenta na série untitled film stills de Cindy Sherman - Soares, Clebea Lúcia (2016)
This research analyzes the clothing in the work of North American artist Cindy Sherman, focusing on early works of her career and, especially, on the presence and use of the clothing in the making of the series Untitled Film Stills. It is addressed, here, the construction of Sherman’s portraits, through one of its main components: the clothing. To do this, I tried to cast a glance on her early work, observing how the artist discovered that clothes could function on her work as a method to deliver a message to the world; and how experimenting with clothes and makeup was evolving, until it reached the maturity seen in Untitled Film Stills. The situation in which Cindy Sherman photographs Untitled Film Stills series is also discussed in this dissertation, with focus on the important issues of this period, which are reflected in this series: the movement of feminist artists; photography versus painting; the appropriation of media images. From groups that refer to certain stereotypes, selected from the series, the analysis started from the principle that clothing is subject to other elements, such as theatricality, the scenarios, pose, makeup and framing. We also noticed how the clothing was, often, the guiding element for the development of the characterization of a character. It was also of our interest, here, to realize how the clothing, as an additional factor, which once was in decay, in portraits, can be a revisited and revised manner of expression in contemporary art.